Role of Organizational Culture on Relationship between Knowledge Management and Teacher’s Performance for National Security - Hussaini, Aminu; Shehu, Mansur; Garba Dagawa, Bello (Edukasiana: Jurnal Inovasi Pendidikan, 2023)
The safety and security of any nation depend on its organizational culture, knowledge management and teachers’ performance. Good organizational culture leads to good performance, likewise, knowledge management helps in improving good organizational culture which in general can lead to safety and security in any State. This paper explores the role of organisational culture in the relationship between knowledge management and teacher’s performance for national security. The study has two research objectives and two research hypotheses. The study adopted a quantitative research design. The population was 7986 out of which 370 were selected. The sample was selected using a multi-stage sampling technique. The data was collected via a questionnaire. Survey questionnaires were distributed and analyzed using Smart PLS (4.0) statistical software. The findings revealed a positive relationship between knowledge management and teacher performance. It further highlights the importance of effective knowledge acquisition, sharing, storage, and application processes. Equally, the moderating role of organizational culture indicates that a strong and supportive culture enhances the impact of knowledge management on teachers’ performance. The study recommends among others that; government and educational administrators in Sokoto State should model cultural values and take responsibility for nurturing the desired culture. The Ministry of Education should put in place policies promoting effective teacher management and engagement, which are critical for developing a positive image for any educational organisation and creating a strong organisational culture.